Noncarious cervical lesions: from etiology to treatment - Ady Coutinho Solino; Walkiria Mendes Lima; Fernanda Villas Boas Tavares; José Lincoln de Queirós Junior; Paulo Márcio Yamaguti; Jussara Karina Bernadon; Elaine Auxiliadora Vilela Maia (Associação Brasileira de Odontologia, 2018)
Objective: this article aims to review the literature on noncarious cervical lesions, from etiology to treatment, considering it a multifactorial disease. Material and Methods: This was a literature review on noncarious cervical lesions, using the PubMed database and the Google Scholar search tool in 2017 and 2018. This research also employed a textbook on the subject as a basis. Results: the literature cited in the article showed that although there is no consensus, mechanical stress and biocorrosion seem to play a major role in the formation and progression of these lesions. Conclusion: further studies with standardized methodologies are needed to help explain the etiology of noncarious cervical lesions.